Livelihood resilience among street hawkers during Covid-19 lockdown in the Awutu Senya East Municipality, Ghana - Adjoa Afriyie Poku; Kofi Sarkodie; Joe Mensah; Richard Sam-Mensah; Jesse Jones Quayson; Kwasi Poku (Journal of Humanities and Applied Social Sciences)
Purpose – The study assesses the livelihood resilience strategies among street hawkers during COVID-19 lockdown in the Awutu Senya East Municipality in Ghana. Design/methodology/approach – Using the explanatory case study approach, 12 participants (hawkers) were sampled with the aid of the purposive and convenience sampling techniques. An interview guide was used to collect data. Findings – The study found that street hawking business, prior to the COVID-19 lockdown was a lucrative venture. The COVID-19 lockdown however had mental, psychological and economic effects on the street hawkers in ASEM causing stress, anxiety. loneliness, loss of business capital, and loss of jobs. Hawkers nevertheless demonstrated resilience in their psychological well-being by adopting strategies such as patronizing digital/social media platforms for funny content and entertainment. Hawkers also showed economic resilience through selling products on digital/social media platforms, relied on personal savings, received social support from family members and religious bodies. Government policies and interventions in the form of free water and electricity played a crucial role in building resilience of street hawkers during the COVID-19 lockdown. Practical implications – The study shows that hawking is a vital avenue for entrepreneurial engagement reducing barriers to entry in formal trading, hence should be considered as key economic venture in the country’s economy. Again, the findings of the study deepen the understanding of stakeholders on the effects of COVID-19 on the psychological and economic life of street hawkers and offers insights into managing both psychosocial and financial stress during crises, emphasizing the potential benefits of resilient strategies for more effective crisis management. The study findings provide insights for government and policymakers on the experiences and coping mechanisms of the vulnerable groups and communities, particularly hawkers during the pandemic. Originality/value – The study qualitatively assesses the psychological and economic effects of the COVID-19 lockdown and the livelihood resilience strategies employed by street hawkers during the COVID-19 lockdown in ASEM, Ghana.